Early Cretaceous dinosaur and other tetrapod tracks of southwestern China - Xing, Lida; Lockley, Martin G. (Science bulletin (Beijing), 2016)
In recent years the Lower Cretaceous red beds of southwestern China have yielded more than 20 significant dinosaur-dominated tracksites. More than half occur in the Jiaguan Formation with the remainder in the Feitianshan and Xiaoba formations. Collectively these sites provide evidence of at least 13 distinct dinosaurian trackmaker morphotypes, in addition to two avian theropod (bird) morphotypes and pterosaur and turtle tracks. Together these total 17 morphotypes provide a data base of 479 potential trackmakers, probably representing the same number of individuals. Such an ichnological database provides a useful proxy paleoecological census of tetrapod communities in the area during the Early Cretaceous, and is especially significant given the complete absence or scarcity of skeletal remains reported from these formations. The composition of ichnofaunas in all three formations is heavily saurischian (theropod and sauropod) dominated with a high diversity of distinctive theropod morphotypes, mostly assignable to known ichnogenera. Moreover, ichnofaunal data from multiple sites are generally consistent between sites and an indication of the reliability and repeatability of track census data. Such regionally-widespread data are rapidly superseding the information available from the skeletal record in the corresponding area, and must therefore be considered of high paleontological value.